Entoloma punjabensis sp. nov. of Rusticoides group from Chichawatni Forest, Pakistan - Fatima, Nadia; Usman, Muhammad; Khalid, Abdul Nasir (Phytotaxa, 2023)
A new species of Entoloma is described from Punjab, Pakistan. Species description is based on morpho-anatomical characterization of basidiomata and molecular phylogenetic analyses of ITS and 28S LSU region of nuclear ribosomal DNA. Entoloma punjabensis sp. nov. is distinguished by light gray to dark brown smooth pileus with crenate margins, reddish to brown central depression, larger globose to subglobose basidiospores 8.5–13.4 × 7.2–11.5 µm and hyaline hyphae of pileipellis.